2018
DOI: 10.31661/jbpe.v0i0.842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Heart Rate Variability in Patients with Heart Failure After Percutaneous Coronary Intervention

Abstract: Background: This study aims to evaluate the effect of exercise training on heart rate variability (HRV) and to determine the correlation between parameters of HRV and the ejection fraction in patients with heart failure after percutaneous coronary intervention.Material and Methods: Fifty patients with left ventricular ejection fraction ≤ 40% undergone percutaneous coronary intervention were randomly allocated in either an exercise training (ET) group or a control group. The ET group performed exercise training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The impact of exercise training on HRV parameters in healthy individuals, athletes and patients with cardiovascular diseases is well established [ 14 , 15 , 16 ], whereas the comparative effects of different exercise modalities in CAD are less well defined. So far, studies have shown that land-based exercise protocols can increase selected time-domain linear HRV parameters, suggesting beneficial effects on cardiovascular health in patients after myocardial infarction or revascularization [ 14 , 17 , 18 ]. Conversely, ours is the first trial to compare HRV changes in CAD after water-based training, land-based training, or unsupervised exercise routines.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of exercise training on HRV parameters in healthy individuals, athletes and patients with cardiovascular diseases is well established [ 14 , 15 , 16 ], whereas the comparative effects of different exercise modalities in CAD are less well defined. So far, studies have shown that land-based exercise protocols can increase selected time-domain linear HRV parameters, suggesting beneficial effects on cardiovascular health in patients after myocardial infarction or revascularization [ 14 , 17 , 18 ]. Conversely, ours is the first trial to compare HRV changes in CAD after water-based training, land-based training, or unsupervised exercise routines.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggested that reductions in HRV and vagal activity were associated with low muscle mass and high fat in overweight individuals which increased the risk of adverse cardiovascular events [ 4 ]. Most studies showed that traditional exercise, such as aerobic exercise and resistance training might improve vagal activity and were helpful to reduce the risk of cardiovascular disease and sudden cardiac death [ 5 ]. However, most obese patients have sedentary habits and poor exercise tolerance due to physical constraints, musculoskeletal discomfort, and lacking of self-motivation, which may prevent them from participating and adhering to traditional physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular and hemorrhagic complications are the most common adverse events post PCI treatment, what's more important is that they are also fatal complications in STEMI patients, for instance, the atrial fibrillation, heart failure and stroke caused by intracranial hemorrhage [18][19][20][21][22][23]. In a previous clinical trial, the proportions of deaths, post-infarction angina, re-infarction/ reocclusion and emergency revascularization were 4.48, 15.2, 4.21, and 8.27% in STEMI patients treated by prourokinase during PCI [6].…”
Section: Discussionmentioning
confidence: 99%